Implementation Of The School’s Vision And Mission to Learners through Habituation of School Culture - Fradana, Ahmad Nurefendi; Ananta, Galuh Nela; Annabila, Pramesti Sintia; Sari, Shintia Dwi Puspita; Nuraimy, Fani Rizkia; Khusnah, Deva Amirotul (Procedia of Social Sciences and Humanities, 2024)
This study aims to describe the Application of the School's Vision and Mission to Learners through Habituation of School Culture. This research uses descriptive methods with qualitative research in the form of direct observation conducted at SD Muhammadiyah 5 Porong, Porong District, Sidoarjo Regency with the research subject of students at the Elementary School. The results of this study include the existence of positive habituation practices where positive habituation practices are one way to implement school culture, the existence of ceremonial activities that are usually carried out in the school environment. Development of School Rules and Regulations by establishing school rules and regulations with the aim of having a positive impact on students or school residents. Through the socialization of the vision and mission of coaching the school culture will be easier to run, Extracurricular Activities, Culture and Character Development Development of national character. Building open communication between students and teachers, Identifying Values and Principles, Rewarding Achievements and Positive Behavior of students, Developing positive Character and Ethics.